2012
DOI: 10.1111/j.1472-4669.2012.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real‐time PCR method for the detection of fossil 16S rDNA fragments of phototrophic sulfur bacteria in the sediments of Lake Cadagno

Abstract: Lake Cadagno is a crenogenic meromictic lake situated in the southern range of the Swiss Alps characterized by a compact chemocline that has been the object of many ecological studies. The population dynamics of phototrophic sulfur bacteria in the chemocline has been monitored since 1994 with molecular methods such as 16S rRNA gene clone library analysis. To reconstruct paleo‐microbial community dynamics, we developed a quantitative real‐time PCR methodology for specific detection of 16S rRNA gene sequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…This sed aDNA constitutes a potential source of information to assess past lake communities (Ravasi et al . ; Stoof‐Leichsenring et al . ; Domaizon et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sed aDNA constitutes a potential source of information to assess past lake communities (Ravasi et al . ; Stoof‐Leichsenring et al . ; Domaizon et al .…”
Section: Introductionmentioning
confidence: 99%
“…The DNA of a variety of taxa, including plants and mammals, can be directly obtained from recent and past sediments (Chariton et al 2010;Hofreiter et al 2012;Pedersen et al 2013;Willerslev et al 2014) even in the absence of visible macrofossils. This sedaDNA constitutes a potential source of information to assess past lake communities (Ravasi et al 2012;Stoof-Leichsenring et al 2012;Domaizon et al 2013), but also species assemblages from the surrounding terrestrial ecosystems (Jørgensen et al 2012;Parducci et al 2013;Pedersen et al 2013). Recent developments of highthroughput sequencing now allow massive sequencing of the ancient DNA contained in sedimentary archives.…”
Section: Introductionmentioning
confidence: 99%
“…The type of identification depends simply on the choice of markers. Similarly, for varietal identification purposes, one can commonly proceed according to protocols derived from the PCR [64][65][66].…”
Section: Pcr Applied To Identificationmentioning
confidence: 99%
“…DNA degradation over time and interactions with living microbial communities could affect the reliability of MOB aDNA results. Indeed, Ravasi et al (2012) reported important DNA degradation in a sediment core covering the Holocene period, leading to drastic decrease in total DNA concentrations over depth in core. Moreover, several studies have reported that active methanotrophic communities can live up to 20 cm deep in sediments of subarctic and arctic lakes (He et al 2012) and deep temperate lakes (Rahalkar et al 2009;Billard et al 2015), leading to potential increase in DNA concentrations and MOB proportions for the topmost part of a sediment core.…”
Section: Mob Adna Analysis: Issues and Future Challengesmentioning
confidence: 99%
“…1200 years) and limited biases due to living microbial communities. Excellent DNA preservation provided by morphological and chemical properties of studied lakes ( Figure S1; deep water anoxia, light, and temperature stratifications; Coolen et al 2006;Corinaldesi et al 2008;Domaizon et al 2013), and the use relative quantification method could prevent effects of changes in aDNA extraction efficiency and aDNA preservation (Ravasi et al 2012) as well as interactions with living microbial communities. Sediment composition can also affect the efficiency of qPCR amplification by co-extracting inhibiting substances (Young et al 2014), but extra purification steps were added to eliminate these potential inhibitors and purify DNA extracts.…”
Section: Mob Adna Analysis: Issues and Future Challengesmentioning
confidence: 99%